2002
DOI: 10.3233/nre-2002-17407
|View full text |Cite
|
Sign up to set email alerts
|

Executive dysfunction following traumatic brain injury: Neural substrates and treatment strategies

Abstract: Executive dysfunction is among the most common and disabling aspects of cognitive impairment following traumatic brain injury (TBI), and may include deficits in reasoning, planning, concept formation, mental flexibility, aspects of attention and awareness, and purposeful behavior. These impairments are generally attributed to frontal systems dysfunction, due either to direct insult to the frontal lobes or to disruption of their connections to other brain regions. Evaluation of executive deficits typically incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(98 citation statements)
references
References 49 publications
2
93
0
3
Order By: Relevance
“…The Coding task has been shown to be highly sensitive to brain impairment (Russell 1972;Crowe et al 1999). Cognitive abilities assessed by the Coding task include sustained attention (Lezak et al 2004), working memory functions (Woo-Sam et al 1971), response speed (Salthouse 1992), perceptual organization (Kaufman 1990), and visual-motor coordination (Sprandel 1995)all executive functions that have been shown to be affected by mTBI (McDonald et al 2002;Demery et al 2010). Current results indicate that the strength of resting state FC in identified visual-frontal networks associated with blast-related mTBI severity may be neural mechanisms that underlie neurocognitive abilities in mTBI.…”
Section: Executive Function and Fcmentioning
confidence: 99%
“…The Coding task has been shown to be highly sensitive to brain impairment (Russell 1972;Crowe et al 1999). Cognitive abilities assessed by the Coding task include sustained attention (Lezak et al 2004), working memory functions (Woo-Sam et al 1971), response speed (Salthouse 1992), perceptual organization (Kaufman 1990), and visual-motor coordination (Sprandel 1995)all executive functions that have been shown to be affected by mTBI (McDonald et al 2002;Demery et al 2010). Current results indicate that the strength of resting state FC in identified visual-frontal networks associated with blast-related mTBI severity may be neural mechanisms that underlie neurocognitive abilities in mTBI.…”
Section: Executive Function and Fcmentioning
confidence: 99%
“…Life expectancy after brain trauma ranges from 40% to over 85% less than https://doi.org/10.1016/j.jns.2020.116711 Received 3 August 2019; Received in revised form 27 November 2019; Accepted 29 January 2020 that of the general population [9]. Several studies have shown that brain trauma can also cause chronic pain disorders [10] and cognitive deficits [11,12]. A recently published meta-analysis of 57 pooled studies reinforced the association between TBI and neuropsychiatric disorders (average odds ratio of 1.67) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Executive function involves various complex cognitive processes, such as solving novel problems, generating strategies or sequencing complex actions (Elliott, 2003). Executive dysfunction in subjects with Traumatic Brain Injury (TBI) has been reported in (Gioia & Isquith, 2004;McDonald, Flashman, & Saykin, 2002) and is believed to be related to a dysfunctional prefrontal cortex (PFC) or disruption in the connection of the frontal lobes and other parts of the brain (McDonald et al, 2002). Poor performance within the PFC of TBI patients, independent of frontal parenchymal lesions, has been reported by researchers (Cazalis et al, 2006;Langfitt et al, 1986;Levin, 1982;Vilkki, 1992).…”
Section: Introductionmentioning
confidence: 99%